(untitled) (Contemporary Mathematics, 2021)
This work deals with the existence of positive continuous solutions for a nonlinear coupled polyharmonic system. Our analysis is based on some potential theory tools, properties of functions in the Kato class Km, n and the Schauder fixed point theorem.